ANALISIS KEPUASAN NASABAH OLEH PELAYANAN PENUKARAN VALUTA ASING BUKAN BANK PT GITA GEMILANG CABANG KUTA KABUPATEN BADUNG - I Gde Oka Saputra; Dewa Putu Yudiana; I Dewa Nyoman Juniasa; I Nengah Suriata (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to figure out customer satisfaction out of the service of PT Gita Gemilang , Kuta branch. In this quantitative research, questionnair whose format was descriptive were distributed  to respondents in order to collect primary data. Based of the analysis, the service provided by this company can be classified as very good. The total  score based on five indicators is in the range from 137 to 168, which is good category. Based on seven indicator, the score is in the range from 169 to 200, which is very good category. The outher suggest that this company improve the category from good to very good and maintain its very good category by improving the quality of its human resources.